2014
DOI: 10.1093/eurheartj/ehu030
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of environmental noise exposure

Abstract: The role of noise as an environmental pollutant and its impact on health are being increasingly recognized. Beyond its effects on the auditory system, noise causes annoyance and disturbs sleep, and it impairs cognitive performance. Furthermore, evidence from epidemiologic studies demonstrates that environmental noise is associated with an increased incidence of arterial hypertension, myocardial infarction, and stroke. Both observational and experimental studies indicate that in particular night-time noise can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
402
2
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 612 publications
(435 citation statements)
references
References 78 publications
11
402
2
20
Order By: Relevance
“…Importantly, the magnitude of the association between noise and depression/anxiety was comparable to the previously reported association of depression with coronary heart disease [2,[29][30][31]. Thus, in addition to direct negative cardiovascular effects of noise [2,[29][30][31] it is tempting to speculate there might be some indirect adverse effect of noise in inducing cardiovascular disease via causing depression and anxiety disorders.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Importantly, the magnitude of the association between noise and depression/anxiety was comparable to the previously reported association of depression with coronary heart disease [2,[29][30][31]. Thus, in addition to direct negative cardiovascular effects of noise [2,[29][30][31] it is tempting to speculate there might be some indirect adverse effect of noise in inducing cardiovascular disease via causing depression and anxiety disorders.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, in addition to direct negative cardiovascular effects of noise [2,[29][30][31] it is tempting to speculate there might be some indirect adverse effect of noise in inducing cardiovascular disease via causing depression and anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of urbanization and industrialization, noise pollution has become a risk factor for neurodegenerative diseases, depression and cognitive decline. Exposure to environmental noise can induce hearing deficit in the auditory system and sleep disturbance [1]. Recently, increasing animal and clinical evidence has shown that chronic noise exposure has obvious effects on cognitive impairment, such as declined memory and learning.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, they considered to be supportive rather than definite due to failure to reach the level of statistical significance [43]. Furthermore, there is a certain degree of heterogeneity among studies regarding the age, gender, mean of assessment/measurement of exposure, duration of exposure, and sound level used, leading to mixed results [44,45]. Here in this study, we found out an association between Body Mass Index group overweight and hypertension.…”
Section: Discussionmentioning
confidence: 65%